Curcuma caesia. Roxb as a Potential Inhibitor of STAT3 and EGFR: a Molecular Docking Approach in Diabetic Nephropathy - Muhammad Farid; Shalahuddin Almaduri; Sujono Riyadi (Universitas Airlangga, 2025)
Background: Diabetes mellitus (DM) is a chronic disorder marked by persistent hyperglycemia, leading to various complications, including diabetic nephropathy (DN). The STAT3-EGFR signaling axis plays a crucial role in the development and progression of diabetic nephropathy, with EGFR activation leading to STAT3 phosphorylation. Curcuma caesia Roxb, rich in curcuminoids, shows promise in managing DN due to its anti-inflammatory and antioxidant properties. This study aims to predict the inhibitory potential of Curcuma caesia compounds on STAT3 and EGFR in DN using molecular docking techniques. Methods: This study utilized molecular docking to evaluate the inhibitory potential of Curcuma caesia compounds on STAT3 and EGFR. Protein structures were obtained from the RCSB database and prepared using Biovia Discovery Studio. Redocking validated the method via RMSD analysis, while docking simulations assessed binding energy (ΔG). ADMET predictions analyzed physicochemical properties and toxicity, ensuring the compounds' suitability as drug candidates. Results: Redocking process validated the method, with RMSD values indicating accuracy. Curcumin (-9.71) and ar-Curcumene (-5.02) showed the lowest binding energy for both proteins, suggesting strong interactions. Visualization revealed significant amino acid interactions, particularly involving hydrogen bonds. Additionally, pharmacokinetic and toxicity analyses indicated that most compounds are suitable drug candidates, exhibiting good absorption, distribution, and safety profiles, thus supporting Curcuma caesia's therapeutic promise in diabetic nephropathy management. Conclusion: Curcuma caesia demonstrates significant potential as a therapeutic agent for diabetic nephropathy, with favorable molecular interactions, strong binding affinity to STAT3 and EGFR, and promising pharmacokinetic and safety profiles.